Preliminary functional characterization, cloning and primary sequence of Fastuosain, a cysteine peptidase isolated from fruits of Bromelia fastuosa - Cabral, H.; Leopoldino, A. M.; Tajara, E. H.; Greene, L. J.; Faca, V. M.; Mateus, R. P.; Ceron, C. R.; Judice, WAD; Juliano, L.; Bonilla-Rodriguez, G. O. (Bentham Science Publ Ltd, 2006)
The present work reports the characterization of Fastuosain, a novel cysteine protease of 25kDa, purified from the unripe fruits of Bromelia fastuosa, a wild South American Bromeliaceae. Proteolytic activity, measured using casein and synthetic substrates, was dependent on the presence of thiol reagents, having maximum activity at pH 7.0. The present work reports cDNA cloning of Fastuosain; cDNA was amplified by PCR using specific primers. The product was 1096pb long. Mature fastuosain has 217 residues, and with the proregion has a total length of 324 residues. Its primary sequence showed high homology with ananain(74%), stem bromelain (66%) and papain (44%).
Keywords: Peptidase; plant peptidase; papain; bromelain; cysteine-protease; protease